A Role for the Chromatin‐Remodeling Factor BAZ1A in Neurodevelopment. Issue 9 (8th July 2016) - Zaghlool, Ammar; Halvardson, Jonatan; Zhao, Jin J.; Etemadikhah, Mitra; Kalushkova, Antonia; Konska, Katarzyna; Jernberg‐Wiklund, Helena; Thuresson, Ann‐Charlotte; Feuk, Lars
Abstract : We identified a non‐synonymous de novo mutation in BAZ1A, encoding the ATP‐utilizing chromatin assembly and remodeling factor 1 (ACF1), in a patient with unexplained ID. The variant is located in an evolutionarily conserved region in the linker motif that connects the PHD domain and the bromodomain (Brd). The mutation affects the expression of genes involved in several pathways including vitamin D metabolism, Wnt signaling and synaptic formation. Our data point to an important role for BAZ1A in neurodevelopment, and highlight a possible link for BAZ1A to ID. ABSTRACT: Chromatin‐remodeling factors are required for a wide range of cellular and biological processes including development and cognition, mainly by regulating gene expression. As these functions would predict, deregulation of chromatin‐remodeling factors causes various disease syndromes, including neurodevelopmental disorders. Recent reports have linked mutations in several genes coding for chromatin‐remodeling factors to intellectual disability (ID). Here, we used exome sequencing and identified a nonsynonymous de novo mutation in BAZ1A (NM_182648.2:c.4043T > G, p.Phe1348Cys), encoding the ATP‐utilizing chromatin assembly and remodeling factor 1 (ACF1), in a patient with unexplained ID. ACF1 has been previously reported to bind to the promoter of the vitamin D receptor (VDR)‐regulated genes and suppress their expression. Our results show that the patient displays decreased binding of ACF1 to the promoter of the VDR‐regulated gene CYP24A1 . Using RNA sequencing, we find that the mutation affects the expression of genes involved in several pathways including vitamin D metabolism, Wnt signaling and synaptic formation. RNA sequencing of BAZ1A knockdown cells and Baz1a knockout mice revealed that BAZ1A carry out distinctive functions in different tissues. We also demonstrate that BAZ1A depletion influence the expression of genes important for nervous system development and function. Our data point to an important role for BAZ1A in neurodevelopment, and highlight a possible link for BAZ1A to ID.